Cognitive rehabilitation for attention and memory in people with multiple sclerosis: study protocol for a randomised controlled trial (CRAMMS) - Lincoln, Nadina; das Nair, Roshan; Bradshaw, Lucy; Constantinescu, Cris S.; Drummond, Avril E.R.; Erven, Alexandra; Evans, Amy L.; Fitzsimmons, Deborah; Montgomery, Alan A.; Morgan, Miriam (BioMed Central, 2015)
Background People with multiple sclerosis have problems with memory and attention. Cognitive rehabilitation is a structured set of therapeutic activities designed to retrain an individual’s memory and other cognitive functions. Cognitive rehabilitation may be provided to teach people strategies to cope with these problems, in order to reduce the impact on everyday life. The effectiveness of cognitive rehabilitation for people with multiple sclerosis has not been established.